T cell-derived exosomes in tumor immune modulation and immunotherapy - Zhou, Qiujun; Wei, Shenyu; Wang, Hui; Li, Yuanyuan; Fan, Shasha; Cao, Yi; Wang, Chenglei (Frontiers in Immunology, 2023)
Exosomes are nanoscale vesicles secreted by most cells and have a phospholipid bilayer structure. Exosomes contain DNA, small RNA, proteins, and other substances that can carry proteins and nucleic acids and participate in communication between cells. T cells are an indispensable part of adaptive immunity, and the functions of T cell-derived exosomes have been widely studied. In the more than three decades since the discovery of exosomes, several studies have revealed that T cell-derived exosomes play a novel role in cell-to-cell signaling, especially in the tumor immune response. In this review, we discuss the function of exosomes derived from different T cell subsets, explore applications in tumor immunotherapy, and consider the associated challenges.